2010
DOI: 10.4103/0974-777x.59246
|View full text |Cite
|
Sign up to set email alerts
|

Looking at complicating non-biological issues in women with HIV

Abstract: Introduction:The increasing number of women acquiring Human Immunodeficiency Virus (HIV) has resulted in a ‘feminization’ of the epidemic. In this article we are reviewing whether females are disadvantaged in the epidemic, due to factors independent of the biological differences in sexes.Materials and Methods:We searched MEDLINE and EMBASE for articles with key words ‘Women’, ‘Gender,’ and ‘HIV’ in any field. The search was restricted to articles published in English within the last 10 years (1999-2009). Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Also congruent with earlier studies (Belle, 1990;Goodman, Smyth, Borges, & Singer, 2009;Sorenson et al, 1996), our findings showed that a lower socioeconomic status was associated with women's risk of experiencing IPV. Potential explanations for this pattern include psychosocial stressors such as poverty, social isolation, homelessness, and unemployment, which have been found to be associated with HIV risk and IPV (Rodrigo & Rajapakse, 2010;Zierler et al, 2000). Additional efforts must be made to reach this population because the problems associated with poverty might limit access to quality health care, HIV testing, and HIV-prevention education (CDC, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also congruent with earlier studies (Belle, 1990;Goodman, Smyth, Borges, & Singer, 2009;Sorenson et al, 1996), our findings showed that a lower socioeconomic status was associated with women's risk of experiencing IPV. Potential explanations for this pattern include psychosocial stressors such as poverty, social isolation, homelessness, and unemployment, which have been found to be associated with HIV risk and IPV (Rodrigo & Rajapakse, 2010;Zierler et al, 2000). Additional efforts must be made to reach this population because the problems associated with poverty might limit access to quality health care, HIV testing, and HIV-prevention education (CDC, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of risk for HIV and STI acquisition among women in sub-Saharan Africa (SSA) is unparalleled (World Health Organization 2011, Magadi 2013). In some parts of SSA, young women have an HIV prevalence eight times higher than men, and the gap in infection prevalence continues to widen (Rodrigo and Rajapakse 2010, Rodrigo and Rajapakse 2010, Stöckl, Kalra et al 2013). Researchers postulate several hypotheses for this gender discrepancy including: early sexual debut among girls (Pettifor, Measham et al 2004, Hallett, Lewis et al 2007), genital inflammation due to untreated STIs (Freeman, Weiss et al 2006, Boily, Baggaley et al 2009, Masson, Passmore et al 2015), bacterial vaginosis (BV) (Myer, Kuhn et al 2005, Chersich and Rees 2008, Hilber, Francis et al 2010, Low, Chersich et al 2011, Cohen, Lingappa et al 2012), intra-vaginal cleaning and tightening practices (Myer, Kuhn et al 2005, Bagnol and Mariano 2008, Hilber, Francis et al 2010, Turner, Morrison et al 2010); and/or high incidence of sexual assault (Abrahams and Jewkes 2010).…”
Section: Introductionmentioning
confidence: 99%